Penerapan Strategi Manajemen dalam Meningkatkan Daya Saing Usaha Mikro Kecil dan Menengah (UMKM) di Era Digital - Abdul Hafiz; Intan Fahzirah; Nadhilah Nazlah Nst; Fitri Hayati (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
This study aims to analyze the application of management strategies in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era, which is characterized by rapid technological advancement and changing consumer behavior. Digital transformation requires MSMEs to adapt by implementing effective, innovative, and market-oriented management practices. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving MSME actors who have utilized digital platforms in their business activities. The findings indicate that the implementation of management strategies, including business planning, human resource management, utilization of digital technology, and digital-based marketing strategies, plays a significant role in improving operational efficiency and business competitiveness. Furthermore, the use of social media and digital marketplaces enables MSMEs to expand market reach and strengthen customer loyalty. However, limited digital literacy and unequal access to technology remain major challenges for some MSMEs. Therefore, continuous support from the government and relevant stakeholders is necessary in the form of training programs, business mentoring, and the provision of adequate digital infrastructure to ensure sustainable competitiveness of MSMEs in the digital era.